High resolution 2D CFD solver based on normalized variable formulation - Perumal S.V.; Yusoff M.Z. (2023)
The study of systems involving fluid flow, heat transfer and associated phenomena using computers is termed as computational fluid dynamics (CFD). The governing equations that define fluid flow phenomena are solved for specific problems using CFD codes. CFD codes comprise three main elements which are preprocessor, solver and postprocessor. The main concern of this research is the solver element. The solver uses information from the preprocessing stage to approximate unknown flow variables by means of functions, discretize governing flow equations and solving the equations. Unstructured meshes are preferred for solving complex geometry problems. Boundedness of the discretization technique is ensured by using High Resolution (HR) scheme which has its roots in Normalized Variable Formulation (NVF). Turbulent flows present new issues such as intermittency, separation and recirculation. These are some phenomena which must be accounted for in extending the current 3D solver to handle turbulent flows. The research methodology involves literature review on CFD equations and turbulent flow theories, numerical discretization and advanced programming techniques. A review of existing 3D code and test runs are necessary to understand the structure of the source code and incorporate extensions. The output from the solver can then be analysed using Techplot 360 which is a postprocessor. 2009 IEEE.